2022
DOI: 10.3390/md20100619
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Genotoxic Potential of the Marine Toxin C17-SAMT Using the In Vivo Comet and Micronucleus Assays

Abstract: The contaminant responsible for the atypical toxicity reported in mussels from Bizerte Lagoon (Northern Tunisia) during the last decade has been characterized as C17-sphinganine analog mycotoxin (C17-SAMT). This neurotoxin showed common mouse toxic symptoms, including flaccid paralysis and severe dyspnea, followed by rapid death. For hazard assessment on human health, in this work we aimed to evaluate the in vivo genotoxic effects of this marine biotoxin using the classical alkaline and modified Fpg comet assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In proliferating cells, a slight induction of DNA double-strand breaks was observed, as well as an induction of MN formation in TK6 cells, with a strong cytotoxic effect at the highest concentration. In a previous study [18], we have shown that C17-SAMT induced primary DNA damage in the liver of mice treated at a dose of 300 µg/kg b.w/day (three oral administrations in 45 h), which was associated with an elevated number of hepatocytes in mitosis and was an indicator of a regeneration process. The results from both the in vivo and the current in vitro studies are strongly correlated, and further investigation is clearly necessary in order to elucidate the precise molecular mechanisms associated with the toxicity of C17-SAMT; in particular, the effects of this toxin on mitochondrial function.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In proliferating cells, a slight induction of DNA double-strand breaks was observed, as well as an induction of MN formation in TK6 cells, with a strong cytotoxic effect at the highest concentration. In a previous study [18], we have shown that C17-SAMT induced primary DNA damage in the liver of mice treated at a dose of 300 µg/kg b.w/day (three oral administrations in 45 h), which was associated with an elevated number of hepatocytes in mitosis and was an indicator of a regeneration process. The results from both the in vivo and the current in vitro studies are strongly correlated, and further investigation is clearly necessary in order to elucidate the precise molecular mechanisms associated with the toxicity of C17-SAMT; in particular, the effects of this toxin on mitochondrial function.…”
Section: Discussionmentioning
confidence: 88%
“…Cells were grown in William's E medium supplemented with 10% fetal calf serum (FCS), 100 U/mL penicillin, 100 µg/mL streptomycin, 2 mM glutamine, 5 µg/mL insulin, and 50 µM hydrocortisone hemisuccinate. HepaRG cells (passages [13][14][15][16][17][18][19] were seeded at a density of 26,000 cells/cm 2 in 96-well plates.…”
Section: • Heparg Cellsmentioning
confidence: 99%
See 1 more Smart Citation